Evidências de fusão parcial nas rochas do complexo Nova Monte Verde, parte sul do Cráton Amazônico, norte do estado de Mato Grosso - Marques, Ana Carolina Gauer (2015)
The migmatitic rocks are generated at a depth of about 15 kilometers below the earth's crust; parts of these rocks are melted and extracted, returning to the surface in the form of granitic rocks. One of the units that have undergone partial melting and the target of this work is the Nova Monte Verde Complex in the southern part of the Amazonian Craton, northern of Mato Grosso, Brazil. This complex is characterized by a set of metamorphic rocks, which dominate orthoderivated rocks with gneissic and migmatitic structures. The complex can be divided in two parts: melanosome (mafic part) and leucosome (felsic part). It is possible to observe dilatational structures or ‘escape’ structures at the leucosome when partial melting occurs, such as where the neck boudin whereas the melanosome form boudin; leucosome located in extensional shear bands; leucosome situated in an asymmetric foliation boudin; and associated to hinge folds. Through the structures observed this migmatite was classified as a metatexito migmatite. And also the presence of mafic selvedge which is a rich in biotite halo of melanocratic composition. Microscopically the melanosome is composed predominantly of mafic minerals, namely: biotite and lower abundance apatite, titanite, zircon and opaque. The biotite define a prominent foliation. Leucosome has a granoblastic texture with the predominance of felsic minerals, such as quartz, K-feldspar (microcline and oligoclase), and plagioclase (labradorite to bytonita). The material that is the final stage of crystallization is represented by the "eutectic", composed by quartz, plagioclase feldspar and K-grained with optical continuity. This material occurs in the following situations: (1) as with rounded pockets in the matrix form; (2) as thin films along the edge of the grains; (3) schlieren how convex forms, triangular or tetrahedral, that develop in the places where the reagents are present. The geochemical data showed a compositional range from intermediate to acidic (silica varies 62.13% to 76.43%), the geochemistry of leucosome pointed a protolith with a possible composition of the various syenogranite to monzogranite field. The leucosome also shown to be derived from a metapsmítico and metapelítico protolith. I watched the anomaly is noticed two patterns; one indicating an enrichment in minerals feldspar with origin of the primary melt and the other pattern pointing a crystallization derived from evolved anatetec melts. The geochronological determination by Pb-Pb zircon evaporation method gave an age 1764 ± 4Ma, which probably represents the age of migmatization. The TDM age 2262Ma with εNd (t = 1,76Ga) of -0.1 suggests a source of Riaciana age, probably crustal